A mixed-method study to evaluate the knowledge and marshalling of untied funds in rural area - Thakan, Somya; Mehta, Aditya; Verma, Deepika; Singh, Lakhan (International Journal Of Community Medicine And Public Health, 2023)
Background: NRHM provides health facilities with unlimited flexible funds to improve the quality of care, in addition to funds for the upkeep and improvement of health facilities, human resources (contractual appointments), equipment, supplies, and medicine, training, and capacity building. The Untied Funds (to be used at the discretion of the facility in charge, primarily as a contingency fund). This study was conducted to gain a better understanding of the financing strategy, knowledge, facilitators, and barriers to underutilization of untied funds. Methods: A mixed-methods study was carried out to determine the utilisation patterns and knowledge of health workers about untied fund. A qualitative study that used a grounded theory approach to identify the facilitators and barriers to effective use of Untied funds. RHTC-Mandawar and its six subcenters were included in our study. Results: The entire mixed-method study clearly demonstrated the barriers and facilitators observed at the subcenter sites. Because health workers were understaffed and overburdened with work, their knowledge was also alarmingly low. Furthermore, no refresher training was provided to them. Finance, a tricky aspect of this programme, was handled with extreme caution. Conclusions: Before untied funds lapse, they must be reviewed and monitored. Refresher training and detailed guidelines are required before funds can be used to improve the health facility and provide additional services to beneficiaries.